2005
DOI: 10.1111/j.1553-2712.2005.tb00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Motivation for Stopping Tobacco Use among Emergency Department Patients

Abstract: ED patients who use tobacco demonstrate motivation to quit and express interest in receiving interventions to assist them after the ED visit. Previous investigations have observed that ED patients do not attend interventions prescribed after the initial ED encounter. These findings suggest that the development of new models for reinforcing tobacco-use interventions initiated in the ED deserve exploration, such as linking them to a tobacco quitline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…6 In a prior study of emergency room patients, an individual's Ladder score was shown to be significantly associated with a patient's reported intention to quit, number of previous quit attempts, perceived coworker encouragement, and socioeconomic status. 14 …”
Section: Inpatient Interviewmentioning
confidence: 99%
“…6 In a prior study of emergency room patients, an individual's Ladder score was shown to be significantly associated with a patient's reported intention to quit, number of previous quit attempts, perceived coworker encouragement, and socioeconomic status. 14 …”
Section: Inpatient Interviewmentioning
confidence: 99%
“…Several studies have found that adult smokers in the ED are interested in cessation, and in receiving a cessation intervention while in the ED (13)(14)(15)(16)(17)(18)(19). ED patients have moderate levels of nicotine addiction (13,14), typically smoking 10 cigarettes/day (13,14), and 61% to 79% are in the contemplation or preparation stage of change (17,19).…”
Section: Introduction Backgroundmentioning
confidence: 98%
“…ED patients have moderate levels of nicotine addiction (13,14), typically smoking 10 cigarettes/day (13,14), and 61% to 79% are in the contemplation or preparation stage of change (17,19). In the pediatric ED, up to 75% of parents who smoke want to quit within 6 months (20).…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…When children are brought to the emergency department, there is an opportunity for a “teachable moment” in which to give tobacco cessation advice to parents who may be more motivated to quit smoking in order to improve their child's health (Winickoff et al, 2003). In addition, studies have shown that adult emergency department patients are interested in quitting and are willing to engage in a brief tobacco cessation intervention (Bock et al, 2001; Klinkhammer, Patten, Sadosty, Stevens, & Ebbert, 2005). …”
Section: Introductionmentioning
confidence: 99%